2013
DOI: 10.3762/bjoc.9.331
|View full text |Cite
|
Sign up to set email alerts
|

Plakilactones G and H from a marine sponge. Stereochemical determination of highly flexible systems by quantitative NMR-derived interproton distances combined with quantum mechanical calculations of 13C chemical shifts

Abstract: SummaryIn this paper the stereostructural investigation of two new oxygenated polyketides, plakilactones G and H, isolated from the marine sponge Plakinastrella mamillaris collected at Fiji Islands, is reported. The stereostructural studies began on plakilactone H by applying an integrated approach of the NOE-based protocol and quantum mechanical calculations of 13C chemical shifts. In particular, plakilactone H was used as a template to extend the application of NMR-derived interproton distances to a highly f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(41 citation statements)
references
References 31 publications
1
40
0
Order By: Relevance
“…622 A comprehensive study combining computation, chemical derivatisation and NMR studies was used to assign both the relative and absolute congurations of plakilactones G 599 and H 600 from a Fijian Plakinastrella mamillaris. 623 Plakortoxides A 601 and B 602, simplextones C 603 and D 604 and plakorsin D 605 were all isolated from Plakortis simplex (Yongxing Is., S. China Sea) although only 603 showed activity. 624 A two-sponge association between Plakortis communis and Agelas mauritiana (Mooloolaba, Queensland, Australia) yielded a new peroxy acid 606.…”
Section: Spongesmentioning
confidence: 99%
“…622 A comprehensive study combining computation, chemical derivatisation and NMR studies was used to assign both the relative and absolute congurations of plakilactones G 599 and H 600 from a Fijian Plakinastrella mamillaris. 623 Plakortoxides A 601 and B 602, simplextones C 603 and D 604 and plakorsin D 605 were all isolated from Plakortis simplex (Yongxing Is., S. China Sea) although only 603 showed activity. 624 A two-sponge association between Plakortis communis and Agelas mauritiana (Mooloolaba, Queensland, Australia) yielded a new peroxy acid 606.…”
Section: Spongesmentioning
confidence: 99%
“…These deviations, although not as good as the~3% values obtained for 1 H-1 H distances in rigid molecules, are in line with those we have observed previously for conformationally flexible systems with errors arising from DFT energy/population estimations and non-r −6 NOE kinetics of dynamic systems. [5,7] Crucially, ignoring PANIC and using the uncorrected HOESY intensities (Column 4, Table 1) gave a substantially less good fit (MAD 8.0%, SD 9.7%) with maximum deviation of 22.5% for H12' to F20.…”
Section: Resultsmentioning
confidence: 99%
“…Of particular relevance, here is the use of through-space interproton contacts from 1 H-1 H NOESY experiments, helping to elucidate molecular structure, conformation, and relative stereochemistry. [5][6][7][8][9][10] Arguably, this technique is the most valuable experimental technique for measuring the crucial conformational dynamics of drug molecules in solution, due to the strong nonlinear distance dependence, which can make it sensitive to vanishingly low levels of minor conformers. [11] We have recently demonstrated that 1 H-1 H NOESY analysis of small molecules can give accurate quantitative interproton distances, building on improvements in NMR hardware, NOE experimental methods, and data analysis.…”
Section: Introductionmentioning
confidence: 99%
“…The 3D structures of 1 and 2 obtained from molecular mechanics methods were further refined at the DFT theoretical level by using MPW1PW91 functional and the 6‐31G(d) basis set. The DFT‐optimized structures were used for the single‐point 1 H and 13 C chemical shift calculations with the same functional and the 6‐31G(d,p) basis set.…”
Section: Methodsmentioning
confidence: 99%